Media Pembelajaran Pendidikan Agama Islam “E-Course” Melalui Penerapan Model Ashyncronous - Milla Sulistya Wardhani; Aminatuz Zahroh (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2022)
This study is the application of e-course learning media through the asynchronous model in Islamic Religious Education subjects at SMK Negeri 2 Lumajang which aims to determine the application of e-course learning media through the asynchronous model in subjects and to find out its implications. This research uses qualitative methods, namely by conducting observations, documentation, and interviews. The results showed that with the application of the e-course learning media through the asynchronous model that students preferred it because the e-course contained varied teaching materials, not only presented literacy material, but also in the form of interactive learning videos connected to social media accounts, and can be accessed at any time. Implications in the application of e-course learning media through asynchronous models, being able to foster creativity, hone teacher skills in assimilation with digitalization of education, in an effort to overcome student boredom during online learning. On the other hand, in the affective aspect, the decrease in the inner bond between teachers and students and teachers who have not grown awareness to be ready to collaborate with technology feel burdened in preparing materials while online (In the Network).